2008
DOI: 10.1002/hep.22075
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine versus lamivudine in Chinese patients with chronic hepatitis B: Results at 1 year of a randomized, double-blind trial

Abstract: Chronic hepatitis B and its life-threatening sequelae are highly prevalent in China. There is a need for effective new therapies to suppress hepatitis B virus (HBV) replication and ameliorate liver disease. In this study, we compared the efficacy of telbivudine, a nucleoside analogue, with lamivudine in Chinese patients. In this phase III, double-blind, multicenter trial conducted in China, 332 patients with compensated hepatitis B e antigen (HBeAg)-positive or HBeAg-negative chronic hepatitis B were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(136 citation statements)
references
References 27 publications
6
130
0
Order By: Relevance
“…HBeAg seroconversion rates as high as 25% have been reported at 1 year of telbivudine treatment in Asian patients with HBeAg-positive CHB [52]. At 2 years of telbivudine and entecavir treatment, HBeAg seroconversion rates are comparable with those achieved at 24 weeks after a 48-week course of PegIFN in patients with HBeAgpositive CHB [21,23,55].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 87%
See 1 more Smart Citation
“…HBeAg seroconversion rates as high as 25% have been reported at 1 year of telbivudine treatment in Asian patients with HBeAg-positive CHB [52]. At 2 years of telbivudine and entecavir treatment, HBeAg seroconversion rates are comparable with those achieved at 24 weeks after a 48-week course of PegIFN in patients with HBeAgpositive CHB [21,23,55].…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 87%
“…The GLOBE study, conducted in 20 countries, compared these two antiviral agents in 1,367 patients (921 HBeAg positive) [22]. A similarly designed study was conducted in China and enrolled 332 patients (290 HBeAg positive) [52]. The HBeAg-positive patients were eligible for discontinuation of therapy if they had received antiviral treatment for more than 1 year and had HBV-DNA levels of \5 log 10 copies/ml (2 9 4 log 10 IU/ ml), with HBeAg loss maintained on treatment for 24 weeks or more.…”
Section: Treatment-induced Hbeag Seroconversion and Disease Progressionmentioning
confidence: 99%
“…For patients with fulminant disease, where a rapid fall in HBV DNA is desirable, a balance has to be found between the need for antivirals, the potential for drug toxicity, and the risk of selecting HBV and HIV drug resistance. Telbivudine in the short term is thought to be safe [145] and, although HBV resistance is likely, probably will not interfere with future ART. The addition of adefovir may theoretically improve efficacy and reduce the risk of telbivudine resistance, although there is no research evidence for this.…”
Section: Acute Hepatitis Bmentioning
confidence: 99%
“…The second year of the GLOBE trial reported viral breakthroughassociated resistance rates of 25% and 11% in HBeAg-positive and HBeAg-negative patients, respectively (47). In 2008, Hou et al (58) compared LtD efficacy with LAM in CHB HBeAg-positive Chinese patients and reported 7.5% and 14.7% 1-year resistance rates in LtD-and LAM-treated groups, respectively. Recently, comparing ETV and LtD anti-viral efficacy in 151 treatment-naïve patients with HBV-related cirrhosis, a significantly higher rate of resistance was found after 2 years of treatment in patients treated with LtD compared to those treated with ETV (27.3% vs. 0%; p=0.0001) (49).…”
Section: Resistance Ratementioning
confidence: 99%